Characteristics of a proliferation of Arenaeus mexicanus (Gerstacker) (Brachyura, Portunidae) in the Ancon shallow waters - Cornejo, Oswaldo (1998)
During the "El Niño" 1982-83 event, the sand crab Arenaeus mexicanus invaded the sand beaches of the central coast of Peru and remained for a year after the event finished, therefore we reported the characteristics of this proliferation. Over 16 months we studied the specie, covering the "Niño" and Post-Niño periods, during the first the population increased rapidly, afterwards tend to stabilize, in the second the population decliroccur a recruitment in April of 1984. The impact over the sand bottom community consisted principally in the intense predation of Semimytilus algosus (for individuals with crab carapace length under 55 mm) and Emerita análoga (over 55 mm); and the competence by food with benthos feeders fishes like Menticirrhus ophicephalus and Stellifer minor.